Leadership Refreyming in sports management: how «to be beyond» - Y. V. Petrikeyeva (Путеводитель предпринимателя, 2020)
The article is approached to leadership in modern management and such term as » reframing leadership» is introduced. The concept of «reframing» on the example of a specific leaders in sports industry is revealed. It also emphasizes on the importance of applying all four types of leadership in the management of a team, a group of people in sports organizations.